PREDIKSI UMUR RENCANA PERKERASAN DENGAN MELAKUKAN PELAPUKAN ASPAL JANGKA PENDEK DAN JANGKA PANJANG SIMULASI DI LABORATORIUM - Tjitjik w Suroso (Direktorat Bina Teknik Jalan dan Jembatan, 2009)
The life of asphalt in pavement dependson asphalt resistence used gainst aging during heating and mixing in asphalt plant and service impacted by weather, sun shine, oxidation and asphalt layer thichness. Asphalt aging occurs during heating and mixing is category zed as shout term aging, and the second to pavement service lipe. The article present the result of short term asphalt aging laboratoryresearch with specimen thickness of 3,4,7.5,9,10.5 and 12 Âµ using RTFO (Rolling thin Film Oven) describing asphalt aging and hardening after asphalt taken out of asphalt mixing plant. Far long term aging, pressure, aging vessel (PAV) was used to take simulation test. This method can be applied to predict asphalt life in pavement (asphalt resistance against hearing and oxidation) Result from research can be used to predict of asphalt life in pavement using the following mathematical model : ([(Pen Pav-20) + 1] x 5 years)/((Pen RTFO-Pen PAV)) Based on aging test using Pressure Aging Vessel, 5 years of asphalt life in pavement can determine the pavement life in given asphalt layer thickness in aggre gate or asphalt layer thickness in aggregate can be calculated.